Book Reviews (Journal of Contemporary Studies, 2025)
1. Nuclear Arms Control in South Asia Politics, Postures, & Practices2. Kashmir: The Unfinished Agenda of Partition3. Rethinking International Political Economy4. Geopolitics and Democracy: The Western Liberal Order from Foundation to Fracture